THE INTRA-FAMILY TAX SAVING DEVICE. - Galitzer, Philip (The Accounting Review, 1944)
One of the chief problems that concern the average taxpayer in the U.S. is that dealing with income taxes. The satisfactory solution of his Federal income tax puzzle will, of course, have its favorable concomitant effects on other related taxes and business problems. If the taxpayer can avail himself of a bona fide transaction whereby the net profits can be divided, the resultant saving to the recipient, arising through the application of lower graduated surtax rates, becomes obvious. One tax-saving expedient often encountered is the legitimate family partnership. Spreading the taxable income invariably results in tax saving. The author has offered suggestions which may be helpful on the subject of acceptable intra-family arrangement as a tax-saving device. One suggestion is that a partnership certificate should be drawn with meticulous care and be duly executed according to legal requirements. Copies of returns for income and all other tax purposes relative to the partnership business should be available.